Will and poetry in the poetry of Thomas Hoccleve - Gibney, David (Trinity College (Dublin, Ireland). School of English, 2016)
This thesis investigates the ways in which Thomas Hoccleve's writing is conversant with the contested area of the human will, and its manifestation in diverse kinds of love. It originates at the nexus of two systems distinct from, but related to, the literary' one that Hoccleve traditionally inhabits - one semiotic and material, motivated by the discovery of his personal seal a number of years ago; the other philosophical and religious, prompted by scholarly attempts to characterize Hoccleve's poetry as 'infected by both theological and scholastic skepticism.' The first and second chapters investigate these contexts. The first analyzes the aesthetic and ethical significance of Hoccleve's seal, and medieval theological approaches to the human will as an affective and rational phenomenon. The second chapter seeks to broaden Hoccleve’s common ascription as 'Chaucerian' by suggesting a Langlandian influence, before examining his interest in knowledge, wisdom, and governance in La Male regle in light of this.
Keywords: English, Ph.D.; PhD Trinity College Dublin, 2016